Исследование приемно-выпрямительных элементов ректенн - Лобазов, Е. А. (ХНУРЭ, 2012)
In this paper calculation of overall receiving-rectifying elements’ characteristic and selection of their optimum configuration was made. Results of calculation is given from the viewpoint of calculating efficiency.